If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 2)(x + 1) + (1 + -3x)(x + 5) = 0 Reorder the terms: (2 + 3x)(x + 1) + (1 + -3x)(x + 5) = 0 Reorder the terms: (2 + 3x)(1 + x) + (1 + -3x)(x + 5) = 0 Multiply (2 + 3x) * (1 + x) (2(1 + x) + 3x * (1 + x)) + (1 + -3x)(x + 5) = 0 ((1 * 2 + x * 2) + 3x * (1 + x)) + (1 + -3x)(x + 5) = 0 ((2 + 2x) + 3x * (1 + x)) + (1 + -3x)(x + 5) = 0 (2 + 2x + (1 * 3x + x * 3x)) + (1 + -3x)(x + 5) = 0 (2 + 2x + (3x + 3x2)) + (1 + -3x)(x + 5) = 0 Combine like terms: 2x + 3x = 5x (2 + 5x + 3x2) + (1 + -3x)(x + 5) = 0 Reorder the terms: 2 + 5x + 3x2 + (1 + -3x)(5 + x) = 0 Multiply (1 + -3x) * (5 + x) 2 + 5x + 3x2 + (1(5 + x) + -3x * (5 + x)) = 0 2 + 5x + 3x2 + ((5 * 1 + x * 1) + -3x * (5 + x)) = 0 2 + 5x + 3x2 + ((5 + 1x) + -3x * (5 + x)) = 0 2 + 5x + 3x2 + (5 + 1x + (5 * -3x + x * -3x)) = 0 2 + 5x + 3x2 + (5 + 1x + (-15x + -3x2)) = 0 Combine like terms: 1x + -15x = -14x 2 + 5x + 3x2 + (5 + -14x + -3x2) = 0 Reorder the terms: 2 + 5 + 5x + -14x + 3x2 + -3x2 = 0 Combine like terms: 2 + 5 = 7 7 + 5x + -14x + 3x2 + -3x2 = 0 Combine like terms: 5x + -14x = -9x 7 + -9x + 3x2 + -3x2 = 0 Combine like terms: 3x2 + -3x2 = 0 7 + -9x + 0 = 0 7 + -9x = 0 Solving 7 + -9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -9x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -9x = 0 + -7 -9x = 0 + -7 Combine like terms: 0 + -7 = -7 -9x = -7 Divide each side by '-9'. x = 0.7777777778 Simplifying x = 0.7777777778
| -3(3p+3)=2(4p+1) | | 126=h^3+7h^2+12h | | 4y=-8x-16 | | 24c^2-150=0 | | 2(3y-5)=4(-2y+2) | | x^2+y^2-4y+20=0 | | (i)6x-9-2(1-x)=x+9 | | 3a^2=-9a+9 | | 108=2(6+l+w) | | 5n+3(4-5n)+3(3n+3)+8(4n-3)= | | 12n^2-5np-2p^2=0 | | -3y-2=5y-9 | | 4b^2+13b-12=0 | | x^2+x-371=0 | | 10a^3+44a^2-30a= | | (7x+7)(7x^2+8x+3)= | | 12t+4(1-4t)= | | f(x)=5x+25x^2 | | d=7x-5 | | 4x^4-13x^3-13x^2+28x-6=0 | | 8c-3=2c+4 | | 2(x+3)(x+3)=12 | | 1.4x+18=6 | | V=2pisquared*h | | -14(q-6)= | | X(15+x)=36 | | 6+4x=x-2 | | X(15*x)=36 | | 0=123t-16t^2 | | 4(y+7)=6y+28 | | s=92x(1.8)t | | 2lnx=mx^2+1 |